2020
DOI: 10.21203/rs.3.rs-25561/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Peptidome Analysis of Cerebrospinal Fluid in Neonates with Hypoxic-Ischemic Brain Damage

Abstract: Hypoxic-ischemic brain injury (HIBD) causes neonatal death and serious neurological disability; however, there are currently no promising therapies for it excepting cooling. Therefore, in this study, we used peptidome analysis to identify differentially expressed peptides in cerebrospinal fluid (CSF) of neonates with HIBD or controls, which may give a foundation for finding new promising drugs of neonatal HIBD. CSF samples were collected from neonates with HIBD (n = 4) or controls (n = 4). ITRAQ LC-MS/MS was u… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…us, a pyroptosis inhibitor was applied to rats with HIE, and its ability to alleviate injury severity was confirmed [30]. It was also demonstrated that the level of the HSP90α/HSP90AA1 peptide in the cerebrospinal fluid (CSF) of neonates with hypoxic-ischemic brain damage (HIBD) was reduced by peptidome analysis, and this peptide was involved in the NOD-LIKE receptor (NLR) signaling pathway [28]. Briefly, NLRP3-activated apoptosis plays a critical role in the pathophysiology of CP induced by HI and leads to brain damage [30].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…us, a pyroptosis inhibitor was applied to rats with HIE, and its ability to alleviate injury severity was confirmed [30]. It was also demonstrated that the level of the HSP90α/HSP90AA1 peptide in the cerebrospinal fluid (CSF) of neonates with hypoxic-ischemic brain damage (HIBD) was reduced by peptidome analysis, and this peptide was involved in the NOD-LIKE receptor (NLR) signaling pathway [28]. Briefly, NLRP3-activated apoptosis plays a critical role in the pathophysiology of CP induced by HI and leads to brain damage [30].…”
Section: Discussionmentioning
confidence: 92%
“…NLRP3 inflammasome activation and pyroptosis have been described in neonatal hypoxic-ischemic encephalopathy [28][29][30][31]. When danger signals (such as ischemia and hypoxia) appear, NLRP3, an intracellular sensor, is able to recognize these signals and forms and activates the NLRP3 inflammasome [32].…”
Section: Discussionmentioning
confidence: 99%
“…Compared to traditional drugs, peptide drugs have several bene cial properties such as less toxicity, accumulation in tissue and drug-drug interactions, and high biological and structural diversity [6]. Our previous study has shown that a 2671.5Da peptide (HSQFIGYPITLFVEKER) was decreased in the cerebrospinal uid of neonatal HIBD and we named it Hypoxic-Ischemic Brain Damage Associated Peptide (HIBDAP) [7].…”
Section: Introductionmentioning
confidence: 99%